2022
DOI: 10.1002/cre2.698
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for medication‐related osteonecrosis after tooth extraction in cancer patients—A systematic review

Abstract: Objectives: Antiresorptive medication has been reported to be associated with medication-related osteonecrosis of the jaw (MRONJ). This systematic review aims at investigating the incidence of and risk factors for MRONJ after tooth extractions in cancer patients treated with high-dose bisphosphonate and denosumab (BP and DS).Material and Methods: The protocol followed the PRISMA statement list and was registered in PROSPERO. Searches were performed for literature published up to April 2021 in the electronic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 36 publications
2
21
0
1
Order By: Relevance
“…Similarly to previous reports, 15,27,32,33 at multivariate analysis (Table 3), we found MRONJ to be significantly associated with dental treatments (HR = 3.67; 95% CI: 1.95, −6.88; p = 0.0001), especially dental extraction (HR = 23.40; 95% CI: 12.98–47.18; p < 0.0001) which was found to be the most common event preceding MRONJ onset. In fact, 28 (50%) out of the 56 MRONJ patients had previously had at least one extraction.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly to previous reports, 15,27,32,33 at multivariate analysis (Table 3), we found MRONJ to be significantly associated with dental treatments (HR = 3.67; 95% CI: 1.95, −6.88; p = 0.0001), especially dental extraction (HR = 23.40; 95% CI: 12.98–47.18; p < 0.0001) which was found to be the most common event preceding MRONJ onset. In fact, 28 (50%) out of the 56 MRONJ patients had previously had at least one extraction.…”
Section: Discussionsupporting
confidence: 89%
“…5,30 A recent systematic review and meta-analysis of randomized controlled trials has reported an incidence of MRONJ in cancer patients under treatment with Dmab which ranged from 0.5% to 2.1% after 1 year, 1.1% to 3.0% after 2 years, and 1.3% to 3.2% after 3 years of exposure. 31 Similarly to previous reports, 15,27,32,33 at multivariate analysis (Table 3), we found MRONJ to be significantly associated with dental treatments (HR = 3.67; 95% CI: 1.95, −6.88; p = 0.0001), especially dental extraction (HR = 23.40; 95% CI: 12.98-47.18; p < 0.0001) which was found to be the most common event preceding MRONJ onset. In fact, 28 (50%) out of the 56 MRONJ patients had previously had at least one extraction.…”
Section: Discussionsupporting
confidence: 80%
“…Complementing these findings, another review specifically focused on cancer patients treated with high-dose BP and DS [15]. This review reported a varying MRONJ incidence rate of 11% to 50% after tooth extractions, emphasizing the significant heterogeneity in the collected data [15].…”
Section: Tooth Extractionmentioning
confidence: 97%
“…Tooth extraction in patients undergoing antiresorptive medication therapy, such as BPs and DS, has been closely scrutinized due to the associated risk of MRONJ. Recent systematic reviews shed light on the incidence rates and risk factors tied to MRONJ following tooth extractions, underscoring the complex interplay between medication use, dental procedures, and patient characteristics [14,15].…”
Section: Tooth Extractionmentioning
confidence: 99%
“…In addition, the use of corticosteroids and concomitant systemic diseases, such as diabetes mellitus, hypertension, renal failure, and immunosuppression, enhance the likelihood of developing MRONJ [ 22 , 23 , 24 ]. Furthermore, invasive dental measures (e.g., tooth extraction), preexisting periodontal inflammation, and prosthesis-related oral mucosal lesions represent significant risk factors for MRONJ, as has also been demonstrated in preclinical research using primarily rodent models [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%